Nonwoven polylactic acid and flax biocomposites. Issue 10 (4th July 2013) - Alimuzzaman, Shah; Gong, R. Hugh; Akonda, Mahmudul
<x xml:space="preserve">Abstract</x> Flax fiber‐reinforced polylactic acid (PLA) biocomposites were made using a new technique incorporating an air‐laying nonwoven process. Flax and PLA fibers were blended and converted to fiber webs in the air‐laying process. Composite prepregs were then made from the fiber webs. The prepregs were finally converted to composites by compression molding. The relationship between the main process variables and the properties of the biocomposite was investigated. It was found that with increasing flax content, the mechanical properties increased. The maximum tensile strength of 80.3 MPa, flexural strength of 138.5 MPa, tensile modulus of 9.9 GPa and flexural modulus of 7.9 GPa were achieved. As the molding temperature and molding time increased, the mechanical properties decreased. The thermal and morphological properties of the biocomposites were also studied. The appropriate processing parameters for the biocomposites were established for different fiber contents. POLYM. COMPOS., 34:1611–1619, 2013. © 2013 Society of Plastics Engineers